Research on the influence mechanism of structural separation on the damage excitation of bridge piers under seismic motion - Yuwen Wen; Yang Liu; Xiaojuan Ning; Houzheng Xia; Wenjun An (PLoS ONE, 2026)
This study builds a special numerical model based on the OpenSees platform, aiming to explore the influence of structural separation on the damage of bridge piers under excitation. The key parameters and threshold conditions related to structural separation were clarified by using simple harmonic excitation. The validity of the established theoretical framework was verified through multiple actual seismic waves, as well as the effect of vertical separation of piers and beams on damage development. At the same time, the damage differences of piers at different heights were compared in combination with vulnerability analysis, with a focus on the regulatory effect of separation on pier failure. The research results show that there is a significant correlation between the excitation parameters and the structural response. Especially when the seismic period approaches the first-order vertical natural vibration period of the bridge, the maximum axial pressure of the bearing increases exponentially with the amplitude, and after the separation occurs, the sensitivity of the collision force to the amplitude is significantly reduced. The working state of bridge piers is significantly affected by seismic waves and the connection form of the bearing type, which leads to regular changes in the structural safety state and failure mode due to the differences in seismic wave characteristics. Meanwhile, the height of the bridge pier plays a key role in the structural response. As the height of the bridge pier increases, the maximum contact force shows a downward trend. However, the vertical separation of the pier and the beam is more likely to cause severe damage or even complete failure of the bridge pier. The above research conclusions provide theoretical references of practical significance for strengthening the seismic design of Bridges.